Functionality of exopolysaccharides produced by lactic acid bacteria in an in vitro gastric system - Mozzi, Fernanda Beatriz (2009)
Aims: To evaluate whether slime-exopolysaccharides (EPS) or capsular-polysaccharide (CPS) production could protect the polymer-producing strains Streptococcus thermophilus CRL 1190 and Lactobacillus casei CRL 87 against the harsh conditions of an in vitro gastric system (GS). EPS stability on the GS was studied. Methods and Results: An in vitro GS model containing human saliva and gastric juice was standardized. Polymer functionality on the cell viability and metabolic activity of the EPS-producing strains in the GS acidic conditions was evaluated. Two isogenic EPS/CPS deficient mutants were used for comparison. EPS or CPS conferred no significant protection on the cell viability of the studied strains after passage through the GS conditions. However, the phospho- and β-galactosidase activities of the EPS+ strains were higher than those of the EPS-. Cytoplasmic alterations in the wild-type and mutant strains and partial degradation of both EPS were detected. Conclusions: The presence of EPS/CPS protected the metabolic activity of the assayed LAB strains, but had no effect on survival at low pH. Significance and Impact of the Study: The presence of EPS/CPS as well as polymer resistance to the harsh conditions of the human GS could impact positively in probiotic strains to exert their properties in the host.